2012
DOI: 10.4021/wjon568w
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Mass: An Initial Sign of Squamous Cell Carcinoma of the Lung

Abstract: Metastatic carcinoma to the testis, excluding lymphoma and leukemia, is an extremely rare condition. The most frequent primary site is prostate cancer. These lesions present clinically either as the first sign of malignancy or more commonly as a complication during the course of known disease. We present the first case of a squamous cell carcinoma of the lung diagnosed with a testicular mass, which is very rarely seen in literature, to our knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…These functions may make invasion and proliferation of metastatic tumor cells difficult. Furthermore, there are two case reports of testicular metastasis of SCC from the lung [8, 9]. Hence, it is important to determine whether the tumor is a primary tumor and other neoplasms should be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…These functions may make invasion and proliferation of metastatic tumor cells difficult. Furthermore, there are two case reports of testicular metastasis of SCC from the lung [8, 9]. Hence, it is important to determine whether the tumor is a primary tumor and other neoplasms should be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, this occurs as a metastasis from the primary cell tumors of the lung, pelvis, or genitals, usually observed in elderly patients. 2,3 In young patients, the most frequent tumors for this localization are germinal cell tumors. It is necessary to exclude teratoma with a somatic malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…In a large retrospective study of 738 autopsies of adult males with solid malignancies, only 5 (0.68%) were shown to have testicular metastases [ 6 ]. Its incidence among all testicular tumors varies between 0.8 and 2.3% [ 3 ]. Patel et al [ 5 ] reported 209 cases of testicular metastases that were primarily identified from an autopsy series and prostate cancer cases from patients who underwent orchiectomy for hormonal therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Gonadal stromal tumors derived from cells that play a role in the development and maturation of sperm comprise approximately 5% of testicular tumors [ 2 ]. With the exception of lymphoma and leukemia cases, testicular metastases are extremely rare, and the majority of testicular neoplasms are primary tumors [ 3 ]. The most frequent primary site that metastasizes to the testes is the prostate followed by lung [ 4 ].…”
Section: Introductionmentioning
confidence: 99%